REKAYASA KONTROL BAGASI KEBERANGKATAN PADA COUNTER CHECK-IN KEBERANGKATAN TERMINAL DUA BANDAR UDARA INTERNASIONAL SOEKARNO HATTA CENGKARENG - Kurnianto, Benny; Novi Mediaswati, Cristina; Agung Wicaksono, Mukhammad; Indra Werdi Sanjaya, Gede; Wijaya Kusuma, Firdaus; Fathan Bagaskara, Fatria (Program Studi Teknik Mekanikal Bandar Udara, 2024)
Baggage control is a critical process in airport operations to ensure the efficient handling and tracking of passenger luggage. The engineering of baggage control at the departure department check-in counter involves the design and implementation of various components and systems. These include baggage conveyor belts, baggage scanning and screening systems, baggage handling software, and integration with airline and airport systems. The baggage conveyor system is a crucial component that transports checked-in luggage from the check-in counter to the sorting area. It consists of a network of belts, rollers, and automated diverters to route the bags to the appropriate destinations. The engineering design of the conveyor system ensures smooth and efficient movement of baggage, minimizing the risk of jams or delays. In conclusion, the engineering of baggage control at the departure department check-in counter of Terminal 2 at Soekarno-Hatta Cengkareng International Airport involves the design, implementation and integration of various systems, technologies and procedures. These engineering efforts aim to ensure the efficient and secure handling of passenger luggage, enhancing the overall airport experience for travelers